Editorial note - Medina Morales, Gladys del Carmen; López Ramos, Arnulfo (Emerging Trends in Education, 2026)
Violence, in its various forms—physical, psychological, symbolic, structural, and digital—represents one of the main contemporary challenges for education systems. Its effects impact school life, socio-emotional well-being, and the educational trajectories of students and teachers. In this context, education is a strategic space for understanding, preventing, and transforming the dynamics of violence, as well as for promoting the construction of a culture of peace, justice, and equity.